An integrated MCDM approach to evaluating global and regional airline performance - Kasım Kiracı (Transport Economics and Management)
Airlines are the fundamental components of air transportation, which plays a critical role in global transportation. The study evaluates airlines' performance using the multi-criteria decision-making (MCDM) approach. The implementation is conducted through an MCDM model. We analyse the financial, risk, and sustainability performance of 30 airlines for the period 2018–2022. The criteria weights were determined using 23 criteria grouped under seven dimensions with the LOPCOW method, and the alternatives were ranked using the TOPSIS method. This study enables a multi-dimensional assessment of airline performance by integrating two dimensions and four criteria related to sustainability and risk into the evaluation framework. Therefore, this study is the first attempt in the literature to simultaneously consider risk factors and multiple environmental criteria. In addition, the performance rankings of the airlines were compared based on their respective regions. The findings reveal that airline performance rankings follows distinct patterns. These patterns were classified into two categories: V-shaped and ∧-shaped. Furthermore, the findings highlighted significant differences in airline performance rankings at the regional level.